Konsinyasi Dalam Pengadaan Tanah Bagi Pembangunan Untuk Kepentingan Umum - Wahyu Ibrahim; Muhammad Yamin; Hasim Purba; Rosnidar Sembiring (Universitas Sumatera Utara, 2019)
Abstract. The problems of this thesis is whether the provisions of the consignment in the procurement of land for the construction of public interest in accordance with the care that is mentioned in the BW / Civil Code, why legally consignment justified in the procurement of land for development in the public interest, and whether care compensation (consignment) of the land used for construction of the public interest is in conformity with the principles of the agreement. This type of research used in this research is a kind of normative juridical research, descriptive analysis. The data analysis was conducted using qualitative analysis. The survey results revealed that the care for damages (consignment) in different land acquisition or do not fit as well as the shift in meaning with care as in the Civil Code, as consignment in land procurement relationship between the government and community objections regarding the huge amount of compensation given, whereas in the Civil Code to repay debt due receivables arising under a contract in an engagement relationship. Keywords: Custody Compensation (Consignment), Land Procurement, Public Interest.